Remanufacturing and e-Waste Management: An Environmental Perspective - Wang, Lan; Rajapakshe, Tharanga; Vakharia, Asoo J. (Production and Operations Management, 2024)
Two empirical observations motivate the focus of this article. First, stemming from the increased demand for electronics, there is a significant change in the number of substitute product offerings. For example, within a product category, Eaton and Dell both offer remanufactured/refurbished products and new products to consumers. Second, to better manage expenses for e-waste, social planners levy fees on producers or consumers of electronic products. Integrating these two aspects, the key issue addressed is whether the social planner should levy a fee on the producer or consumer and whether such a fee should target one or both products. Through a rigorous analysis of the social planner’s fee decision, insights into differences between alternative policy choices are discussed. As expected, if the producer or consumer fee is levied on the same set of products, there are no differences in the impact on all stakeholders. Thus, the social planner would be indifferent in choosing whether to levy a fee on the producer or the consumer. On the other hand, analyzing current policies (e.g., Connecticut collects e-waste management fees from producers based on new product sales while California collects the fees from consumers purchasing new and refurbished/remanufactured products), we find significant differences for all stakeholders. Analytically, we show that pass-through fee effects of each policy are different. Through extensive numerical experiments, we find that the policy of a consumer fee on purchases of both products offers a greater chance of alignment between social planner and producer objectives; there are regions defined by parameters associated with remanufacturing activities where there exists a trade-off between the benefits to producers versus those for consumers; and there exist regions where the optimum policy for the social planner is aligned with the original equipment manufacturer’s preferred policy choice.